K. R. Bradlely, Slavery and Rebellion in the Roman world, 140 b.C.-70 b.C. Londres, B. T. Batsford e Indiana (University Press), 1989, XIII + 186pp. - López Barja de Quiroga, Pedro (Gerión. Revista de Historia Antigua, 1991)
Sin resumen